INDIAN FOLK CULTURE AND COLOR: भारतीय लोक संस्कृति और रंग - Sharma, Sangeeta (International Journal of Research -GRANTHAALAYAH, 2014)
Dr. According to Hazari Prasad Dwivedi - "The meaning of the word Lok is not the district or the village, but the entire people spread in the cities and villages, whose base is not artisans, but people living simple and simple lives." Folk art is an important part of folk culture. It is an identity of culture as far as Indian folk culture is concerned, folk art has special significance in it. The purpose of art can be expression, fame, earning, service, attainment of pleasure, world welfare etc. डाॅ. हजारी प्रसाद द्विवेदी के अनुसार - “लोक शब्द का अर्थ जनपद या गाँव नहीं बल्कि नगरों व गाँवों मे फैली वह समूची जनता है जिसका आधार पोथियाँ नहीं, अकृत्रिम और सरल जीवन व्यतीत करने वाले जन है।“ लोक संस्कृति का अहम भाग है लोक कला। यह संस्कृति का पहचान है जहाँ तक भारतीय लोक संस्कृति की बात है इसमें लोक कला का विषेष महत्व है। कला का प्रयोजन अभिव्यक्ति, यष प्राप्ति, धनोपार्जन, सेवा, आनंद की प्राप्ति, विष्व कल्याण आदि हो सकते है।